How Infrastructures and Practices Shape Each Other: Aggregation, Integration and the Introduction of Gas Central Heating. (June 2023) - Watson, Matt; Shove, Elizabeth
We know that networked infrastructures enable forms of mobility, energy use, and flows of data, and we know that modern life depends on these arrangements. We also know that relations between infrastructures and social practices are recursive, extensive, and multiple. But what of the detail? How do infrastructures shape the many practices to which they relate, and vice versa? The research we describe was designed to address these questions head on. We discuss the arrival and normalisation of gas central heating with reference to householders' experiences and practices and to the ambitions and decisions of utilities and city authorities. In the process, we identify forms of aggregation and of integration on which infrastructure – practice dynamics depend. In taking this approach, we demonstrate the relevance of practice theory for conceptualising and analysing 'large' social phenomena including transitions in energy systems and related patterns of demand.